2013
DOI: 10.1021/ef4015394
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative X-ray Fluorescence Analysis of Biomass: Objective Evaluation of a Typical Commercial Multi-Element Method on a WD-XRF Spectrometer

Abstract: With the increasing utilization and trade of biomass, there is a growing need for quick and reliable quantitative chemical analysis of the inorganic elemental composition of biomass. X-ray fluorescence (XRF) spectrometry performed directly on the raw biomass with limited prior sample preparation is an attractive method to this end. However, reliable calibration of XRF spectrometers for universal multi-element analysis can be very hard to implement mainly due to problems with matrix corrections. XRF users thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
80
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(98 citation statements)
references
References 21 publications
14
80
4
Order By: Relevance
“…In our previous study, we observed -with some exceptions -that below 25 ppm (or below LOD) not all elements are consistently detected in all repeated XRF measurements. 9 The results of the current study are consistent with this observation. Note that some of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27…”
supporting
confidence: 90%
See 4 more Smart Citations
“…In our previous study, we observed -with some exceptions -that below 25 ppm (or below LOD) not all elements are consistently detected in all repeated XRF measurements. 9 The results of the current study are consistent with this observation. Note that some of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 27…”
supporting
confidence: 90%
“…The instrument and method are described briefly below and have been described in detail in our previous study. 9 Blank runs of pellets produced of 10 grams Hoechst Wax C showed the following concentrations: Cl: 81 ppm, Ru: 34 ppm, Cu: 9 ppm, Fe, Zn: 6 ppm and Ni: 5 ppm.…”
Section: Xrf Analysismentioning
confidence: 97%
See 3 more Smart Citations